Oral Manifestations of the Immune Thrombocytopenic Purpura - Bousserouit, Marwa; Hakkou, Fouzia; Chbicheb, Saliha (Integrative Journal of Medical Sciences, 2021)
Introduction: Hemorrhagic oral mucosa lesions are the most common clinical manifestations of immune thrombocytopenic purpura (ITP). Case Report: A 41-year-old female patient consulted the Oral Surgery Department of the Dental Consultation and Treatment Center in Rabat for spontaneous gingivorrhagia. Clinical examination and further examination showed severe thrombocytopenia associated with an anemic syndrome. The diagnosis of ITP was made. Treatment was based on oral corticosteroids and immunoglobulin in the hospital. Conclusion: These manifestations sometimes lead the patient to consult their dental surgeon in the first intention, hence the need to make the diagnosis based on a thorough global examination and refer the patient to an adapted structure.